Pengaruh Marketing Public Relations Terhadap Brand Awareness dan Keputusan Pembelian Mossdoom - Galuh Anisa Putri; Rendra Widyatama (CV. ITTC INDONESIA, 2026)
The development of social media requires companies to implement more interactive marketing communication strategies; however, high digital exposure is not always followed by consumers’ purchasing decisions. This phenomenon can be observed in the local bag brand Mossdoom, which has high content exposure on social media, yet not all audiences necessarily make purchases. In addition, studies examining the simultaneous relationship between Marketing Public Relations, brand awareness, and purchasing decisions within the context of digitally based local fashion brands remain limited. Therefore, this study aims to analyze the influence of Marketing Public Relations on brand awareness and purchasing decisions for the local bag brand Mossdoom, while also examining the role of brand awareness as a mediating variable. This study employed a quantitative approach using a survey method involving 140 female respondents aged at least 18 years old who are active on social media and have been exposed to Mossdoom’s content. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4. The findings indicate that Marketing Public Relations has a positive and significant effect on brand awareness and purchasing decisions. Brand awareness also has a significant effect on purchasing decisions and is proven to partially mediate the relationship between Marketing Public Relations and purchasing decisions. Furthermore, the study found a direct influence of Marketing Public Relations on purchasing decisions, indicating a dual-path influence pattern in digital marketing communication.